Survey on Agile Implementation of the BI Systems - Simi Bajaj, Kamini; Rai, Tressa (International Journal of Engineering and Technology, 2018)
Business intelligence (BI) is a technique that helps organisations to effectively analyse, manipulate and store data. It takes historical and present data from various sources and presents the data to the users anytime, anywhere to help them make smart and effective decisions. However, the cross functional nature of BI systems that covers the length and breadth of the organization, pose an issue with effective implementation. Various Traditional methodologies have been used to implement BI systems however have encountered countless failures leading the practitioners to look up to Agile methodologies to overcome the shortcomings. Since different companies have different requirements, out of the box Agile solutions do not address the requirements effectively. As a result, use of Agile methodologies for BI implementation also face lot of issues. To justify this claim we conducted a survey of agile practitioners doing BI implementation. This paper aims at presenting the findings of the study focused on identifying the gaps in implementing BI systems using Agile methodologies. It also presents the results for the survey conducted to capture the methodologies used by the organisations and practitioners and issues in BI implementation. In future, this captured information would be utilised into formulating a framework that can work along with Agile methodology to help address the issues faced with Agile methodologies for BI Implementations.Â